2014
DOI: 10.1017/s1368980014000603
|View full text |Cite
|
Sign up to set email alerts
|

Impact of peer counselling breast-feeding support programme protocols on any and exclusive breast-feeding discontinuation in low-income women

Abstract: Objective: Peer counselling (PC) programmes have been shown to improve breastfeeding outcomes in populations at risk for early discontinuation. Our objective was to describe associations between programme components (individual and combinations) and breast-feeding outcomes (duration and exclusivity) in a PC programme for low-income women. Design: Secondary analysis of programme data. Multivariable-adjusted Cox proportional hazards models were used to examine associations between type and quantity of peer conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 16 publications
0
9
1
Order By: Relevance
“…Findings in this study regarding the impact of BFPC contact on positive BF outcomes were consistent with other studies. 27,28 Previous studies have reported that WIC BFPC programs support the improvement of BF initiation 24,25,[27][28][29] and duration 22,25,29 with in-person contact being the most effective. While phone conversations and in-person contacts were the most effective in improving BF in the present study, systematic reviews have reported that in-person support was more effective than phone or combined phone and in-person support.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Findings in this study regarding the impact of BFPC contact on positive BF outcomes were consistent with other studies. 27,28 Previous studies have reported that WIC BFPC programs support the improvement of BF initiation 24,25,[27][28][29] and duration 22,25,29 with in-person contact being the most effective. While phone conversations and in-person contacts were the most effective in improving BF in the present study, systematic reviews have reported that in-person support was more effective than phone or combined phone and in-person support.…”
Section: Discussionmentioning
confidence: 99%
“…Further, the impact of specific WIC BFPC program components on BF initiation and duration as has been relatively understudied. [22][23][24][25] Therefore, the purpose of this study was to compare the initiation and duration of BF at 30 days among mothers enrolled in an upstate New York WIC program from April 1, 2009 to March 30, 2011, who accepted a BFPC referral, and received different quantities and types of BFPC support (telephone, in-person, and/or mailings).…”
Section: Introductionmentioning
confidence: 99%
“…Extensive research has shown that early support for infant feeding is critical to the initiation and establishment of successful breast feeding. [31][32][33][34][35][36][37][38][39][40][41][42][43][44] Other reasons for our findings cannot be ruled out. For instance, visits to hospital from relatives may be higher for children born on Saturdays, which might distract from breast feeding counselling.…”
Section: Discussionmentioning
confidence: 99%
“…Some mothers benefit from the support of hospital staff to initiate and successfully establish breast feeding. [31][32][33][34][35][36][37][38][39][40][41][42][43][44] We conducted a retrospective study of breast feeding in the years 2005 and 2010, comparing breast feeding incidence rates by day of week of birth. We postulated that breast feeding may vary by day of week of birth, especially for the babies of the least educated mothers, who are less likely to have access to other sources of support and information not provided at hospital.…”
Section: Introductionmentioning
confidence: 99%
“…17 Women are eligible for the BFI program if they are WIC eligible, and most participants are referred by their local WIC agency. In the BFI program, paid PCs are recruited by community Extension and WIC agencies and are required to have transportation, a high school degree, and a positive breastfeeding experience.…”
Section: Breastfeeding Initiative Programmentioning
confidence: 99%